Gambaran Pola Makan dan Aktivitas Fisik pada Lansia Hipertensi di Posyandu Lansia Desa Tremas Pacitan - Auliya Rahmanda; Eska Dwi Prajayanti (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2022)
Hypertension is a condition when blood pressure is chronically elevated. From the WHO 2021 data, the global prevalence of hypertension is 1.28 million. From the results of the preliminary study, Arjosari District entered the top 3 with the highest hypertension. The main cause of hypertension in the elderly is diet. Hypertensive elderly who experience a decrease in physical function can cause high blood pressure for a long time. The purpose of this study was to describe the pattern of eating and physical activity in the elderly with hypertension at the Elderly Posyandu, Tremas Pacitan Village. This type of research is descriptive. The sample in the study was 50 respondents with a total sampling technique of sampling. The results showed that the diet in the elderly with hypertension was in the sufficient category for as many as 46 respondents (93, 9%) and less than 3 respondents (6.1%). Physical activity in the elderly with hypertension was 39 respondents (79.6%) moderate, 8 respondents (16.3%) severe, and 2 respondents (4.1%) less. The degree of hypertension in the elderly in Tremas Arjosari Village, Pacitan, showed 46 respondents (93.9%) in grade II hypertension and 3 respondents (6.1%) in grade I. The description of the eating pattern of the elderly in Tremas Pacitan Village shows that 93.9% is sufficient and moderate physical activity is 79.6%.